2021
DOI: 10.32413/pjph.v10i4.509
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetes and Hypertension as risk factors with Ischemic Heart Disease among patients visiting a Public Sector Tertiary Care Hospital of Karachi, Pakistan

Abstract: Background: Ischemic Heart Disease (IHD) is a leading cause of morbidity and mortality worldwide. IHD results from myocardial ischemia, and occurs whenever perfusion outgrows the demand. Though lethal, but can be prevented by modification of predisposing conditions, most important are diabetes and hypertension. Almost fifty percent of IHD patients are found hypertensive with or without being diabetic. The objective of the study was to determine association of diabetes and hypertension as risk factors for IHD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…History of anti-hypertensive drugs intake, lower intake of vegetables and fruits, and medication adherence represented the highest levels amongst the risk factors. In this study, males were in majority in both groups and these findings were similar to the study of Shaikh ZA et al [6] as they found that the males were in majority. In this study the continues smokers were in majority in HF cases 38(38.0%) compared to controls.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…History of anti-hypertensive drugs intake, lower intake of vegetables and fruits, and medication adherence represented the highest levels amongst the risk factors. In this study, males were in majority in both groups and these findings were similar to the study of Shaikh ZA et al [6] as they found that the males were in majority. In this study the continues smokers were in majority in HF cases 38(38.0%) compared to controls.…”
Section: Resultssupporting
confidence: 92%
“…Despite advancements in the management of patients being affected by systemic hypertension and the emergence of effective anti-hypertensive drugs, prevalence of HF resulting from hypertension tends to increase in Pakistan [2,3]. In the Pakistani demographics, hypertensive heart failure (HHF) mostly affects adults, resulting in a loss of expertise and low standard of living [5,6]. In recent years, epidemiological investigation for the heart failure risk factors in the general populace has continued although a very little is known regarding the significant risk factors of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…CAD is verycommunalamong patients with diabetes and hypertension as compared to theindividuals with diabetes mellitus or hypertension only, and the progress of atherosclerosis is accelerated with greater fragmentation of atherosclerotic plaques and a low coronary perfusion reserve in diabetic patients along with hypertension. Patients with hypertension and diabetes have abnormal systolic and diastolic functions of the ventricles with congestive heart failure and left ventricular hypertrophy, counterparts those with diabetes or hypertension 23 .…”
Section: Discussionmentioning
confidence: 99%